Borata-Wittig olefination reactions of ketones, carboxylic esters and amides with bis(pentafluorophenyl)borata-alkene reagents. Issue 29 (12th July 2017) - Wang, Tongdao; Kohrt, Sonja; Daniliuc, Constantin G.; Kehr, Gerald; Erker, Gerhard
Abstract : Borata-alkenes containing the B(C6 F5 )2 unit are employed in borata-Wittig olefination reactions. Abstract : The strongly electrophilic borane derivative amino–CH2 CH2 CH2 –B(C6 F5 )2 6 was α-CH deprotonated with LiTMP to give the borata-alkene {[amino–(CH2 )2 –CHB(C6 F5 )2 − ][Li + ]}2 9 which underwent facile [2 + 2] cycloaddition reactions with benzophenone or fluorenone to yield the respective 1, 2-oxaboretanides11a, b . Compounds9 and11 were characterized by the X-ray diffraction. Thermolysis or hydrolysis of compounds11a, b gave the corresponding borata-Wittig olefination products12a, b . A variety of R–CH2 –CH2 –B(C6 F5 )2 boranes (conveniently generated by hydroboration of terminal alkenes R–CHCH2 with Piers' borane [HB(C6 F5 )2 ]) were analogously deprotonated to give the respective borata-alkenes16a–e (R: Ph–CH2 –, n C4 H9, t Bu, Cy, PhCH2 CH2 –). They underwent "non-classical" borata-Wittig olefination reactions with ethylformate to give the respective enolether carbonylation products, or their C1 -elongated aldehydes (after hydrolysis). The borata-alkene [Ph–(CH2 )2 –CHB(C6 F5 )2 − ] [Li + HTMP] (16a ) gave the respective "non-classical" borata-Wittig olefination products, the enolethers25a, b and27, respectively, upon treatment with methyl- or ethyl acetate or γ-butyrolactone.